Relatório de Estágio Profissional "Aprender a ensinar enquanto se ensina" - David Tiago Macedo Teixeira (2018)
The curricular unit, school placement is part of the 2nd year of the Master's Degree in Physical Education Teaching in Basic and Secondary Education of the Faculty of Sport, University of Porto and aims to contribute to the training of future teachers by providing them with knowledge and skills necessary for the exercise of the teaching function. This document, named the Practicum Report, was drawn up in function of this same curricular unit, reporting the experiences acquired in the year of internship, in a reflexive process. The Internship Report is divided into four chapters, the first is the Biographical Framework, which contemplates the reasons why I chose to go into the area of Physical Education and the expectations regarding the year of internship, in a self-reflexive way. The second chapter, concerning the Professional Practice Framework, explores the legal, institutional and functional contexts alluding to the EP. In the third chapter is referenced the Realization of Professional Practice, subdivided into design, planning, teaching and evaluation. Finally, in the fourth chapter of this RE are present the Conclusions and Perspectives for the Future, where are patented the reflections made during the Practicum year, in the form of conclusion, as well as prospects for the future as a teacher and Physical Education professional. KEY WORDS: